Les chants de l’Émigrec - Solange Festal-Livanis (Cahiers Balkaniques)
This article looks at the different ways in which artists and intellectuals living in exile in France relate to the songs of exile since the military junta. The success of concerts and songs on the theme of exile prompts us to ask whether, beyond a commercial convenience for some, these songs would not be a necessary anchoring in the various crises experienced. That song is linked to emotional memory also invites us to wonder whether there is not a nostalgia for the ξενιτιά. We begin by listening to testimonies from exiled Greek musicians whose attitude towards traditional song is ambivalent. In part, we find this ambiguous attitude where nostalgia and distancing from the experience of political exile coexist in the account of Vassilis Vassilikos Καφενείον “Εμιγκρέκ” [Kafenion “Emigrec”]. Furthermore, Yannis Kiourtsakis has placed exile and the relationship with popular culture at the center of his writing. With Σαν Μυθιστόρημα (Le Dicôlon) and Εμείς οι άλλοι (Double exil), he finds a new form to sing the impossible nostos.